The Role of Social Media Marketing on Company Orientation - Rahman, Wahyudin; Aprilian, Muhammad Irfan; Pataba, Sarianti S.; Arda Suari, Ni Gusti Atu (Yayasan Pendidikan Belajar Berdikari, 2024)
This study is a descriptive quantitative study. This study used questionnaires and interviews as its technique of data gathering. MSMEs in Soppeng Regency make up the research population. The minimum sample size required for this study is equal to 12 times the total number of latent variables in the path model, or 12 times the total number of indicators. 114 MSME samples in all made up the study's sample. According to the study's findings, entrepreneurial orientation is positively and significantly impacted by social media marketing marketing capabilities, while entrepreneurial orientation is not impacted by social media marketing marketing assets. Regarding the indirect effects, MSME marketing performance is positively and significantly impacted by Social Media Marketing marketing capabilities through entrepreneurial orientation as an intervening variable, whereas marketing performance is not impacted by Social Media Marketing marketing assets through entrepreneurial orientation as an intervening variable